Coccolithophore Distribution in the Western Black Sea in the Summer of 2016 - Margarita D. Dimiza; Maria V. Triantaphyllou; Alexandra Ravani; Elisa Malinverno; Boris T. Karatsolis; Stella Psarra; Aristomenis P. Karageorgis (Diversity, 2023)
Coccolithophores are an important component of phytoplankton abundance and biomass in the brackish environments of the Black Sea. Here, the abundance, composition, and distribution of coccolithophores were investigated in water samples taken from the first 50 m at 18 stations in the western Black Sea during a coccolithophore bloom, in June 2016. The total cell abundances ranged from 2 to 763 × 104 coccospheres L−1; Emiliania huxleyi was the most dominant species, but also Syracosphaera spp. (S. dilatata and S. molischii), Acanthoica (A. acanthifera and A. quattrospina), and Algirosphaera robusta displayed remarkably high concentrations. The formation of the seasonal thermocline significantly affects the vertical distribution of coccolithophores. Emiliania huxleyi, Syracosphaera spp., and Acanthoica spp. were restricted to the upper part of the water column, whereas high abundances of Algirosphaera robusta occurred below the thermocline. Overall, our results show significant differences in the vertical (ANOSIM R = 0.50, p = 0.0001) and spatial (ANOSIM R = 0.18, p = 0.0006) distribution of coccolithophores. Higher abundances of E. huxleyi and Syracosphaera spp. were recorded in the northwestern inner shelf region when compared to the open-sea samples. The observed coccolithophore spatial distribution is suggested to be mostly associated with the influx of less saline river water with high nutrient concentrations.